Morphometric Characters of Nile Tilapia (Oreochromis niloticus) in Thailand - Piya KOSAI; Piyadon SATHAVORASMITH; Kanitta JIRAUNGKOORSKUL; Wannee JIRAUNGKOORSKUL (Walailak Journal of Science and Technology, 2014)
The present study is conducted to describe the morphometric characteristics of a Thailand strain of Oreochromis niloticus. The total length of the observed fish ranged from 7.96 - 17.36 cm. Body measurement and proportions are extensively used for identification of this species. The following 18 measurements are determined for each fish: Total length (TL); Standard length (SL); Body depth (BD); Pre-dorsal length (PDL); Pre-pectoral length (PPCL); Pre-pelvic length (PPVL); Pre-anal length (PAL); Depth of caudal peduncle (DCP); Length of caudal peduncle (LCP); Head length (HL); Eye diameter (ED); Snout length (SNL); Upper jaw length (UJL); Lower jaw length (LJL); Caudal fin length (CFL); Pectoral fin length (PFL); Length of dorsal fin base (LDFB); Length of anal fin base (LAFB). The rate of growth of different morphological body parts of the fish in relation to its total length is studied. Additionally, the total length and body weight relationship is found to be a straight line in logarithmic scale expressed as Log BW = 3.026 Log TL - 1.839. The value of regression co-efficient obtained for the length-weight relationship is 3.026. This finding suggests that selection for growth using this equation is a good alternative for measuring weight in the field, when accurate weighing balances are not available. Hence, the present study provides the information of the various body parts measurements of Tilapia and establishes mathematical equations relating to these various morphometric relationships which can be utilized for the conversion of one measurement into another.